Effect of Work Environment and Work Motivation on the Performance of Gojek Drivers in the City of Surakarta - Indah Puspita Sari; Agus Suyatno; Khabib Alia Akhmad (International Journal of Asian Business and Management, 2023)
Online transportation is slowly becoming the prima donna in the world of transportation. Especially in the city of Surakarta, Gojek online transportation is ingrained as an online transportation service that performs very well, by providing services using online transportation applying costs that can be said to be cheap, prioritizing customer convenience, cashback and discounts for users. So, from that assessment, new customers will be able to judge by themselves so that it has an impact on feeling safe and calm when choosing online transportation. The purpose of this research is to examine the influence of work environment variables and work motivation variables on driver performance. This research method uses quantitative. The results of this study, work environment variables partially have a positive and significant effect on performance variables and work motivation partially have a positive and significant influence on performance variables. Work environment variables and work motivation variables simultaneously have a positive and significant influence on performance variables